Formation and antibacterial activity of AlOOH/Ag composite coating on macroporous α-Al2O3 ceramics - Senkina, Elena I.; Buyakov, Ales S.; Kazantsev, Sergey O.; Bakina, Olga V.; Krinitsyn, Maksim G.; Lozhkomoev, Aleksandr S. (Coatings)
In this study, the modification of macroporous α-Al2O3 ceramics with AlOOH nanostructures impregnated with silver particles is carried out using bicomponent Al/Ag nanoparticles obtained by the simultaneous electrical explosion of Al and Ag wires. Nanoparticle suspension impregnation of porous ceramics followed by oxidation with water is shown to lead to the formation of a continuous AlOOH nanosheet coating on the ceramic surface, with silver releasing on the surface of nanosheets in the form of individual particles sized 5–30 nm. Modified with AlOOH/Ag nanostructures, macroporous α-Al2O3 pellets with a diameter of 11 mm and a thickness of 5 mm show 100% efficiency for water purification from bacteria with a concentration of 105 CFU/mL for 7.5 min at a flow rate of 6.7 mL/min.